2010
DOI: 10.1063/1.3530122
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow in microvascular networks: A study in nonlinear biology

Abstract: Plasma skimming and the Fahraeus-Lindqvist effect are well-known phenomena in blood rheology. By combining these peculiarities of blood flow in the microcirculation with simple topological models of microvascular networks, we have uncovered interesting nonlinear behavior regarding blood flow in networks. Nonlinearity manifests itself in the existence of multiple steady states. This is due to the nonlinear dependence of viscosity on blood cell concentration. Nonlinearity also appears in the form of spontaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…In this approach, the hemorheological approach is inseparable, since it is well known, that blood and plasma viscosity, hematocrit, red blood cell deformability as well as red blood cell aggregation are major determinants of the microcirculatory flow [e.g. 2,3,10,17,24].…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, the hemorheological approach is inseparable, since it is well known, that blood and plasma viscosity, hematocrit, red blood cell deformability as well as red blood cell aggregation are major determinants of the microcirculatory flow [e.g. 2,3,10,17,24].…”
Section: Introductionmentioning
confidence: 99%
“…We will consider two cases, d C = 5 µm and d C = 10 µm, in order to highlight the role that the diameter of this middle vessel plays in the formation of multiple equilibria and sustained oscillations. Geddes et al (2010) showed that the network under consideration can exhibit multiple equilibria under different plasma skimming and viscosity assumptions than those used here. Their approach centered on plotting the solution curves to Eqs.…”
Section: Equilibriamentioning
confidence: 96%
“…These properties will also affect blood transport and gas diffusion characteristics. The interaction of these phenoma in microcirculatory beds is complex and highly nonlinear, such that it could lead to the presence of chaotic states with spontaneous oscillations in vessel calibre [11]. An important regulator of calibre and tone of retinal blood flow has been found to be nitric oxide (NO) [12].…”
mentioning
confidence: 99%
“…It is not immediately obvious why increases in systolic pressure would be associated with a reduced vasodilatory response to flicker light exposure. One of the possible mechanisms might be related to the interaction of retinal haemodynamics with cerebrovascular and cerebrospinal fluid dynamics [6] as well as the complex particulate properties of blood in small calibre vessels being affected by intravascular flow conditions modulating erythrocyte and plasma separation [11,18].…”
mentioning
confidence: 99%